Pengembangan Variasi Dribbling Sepak Bola Berbasis Vidio di SSB Putra Arema - Masruhin Masruhin; Roesdiyanto Roesdiyanto; Kurniati Rahayuni (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to develop variations of video-based soccer dribbling exercises at SSB Putra Arema that can be used by coaches as a medium for variations of soccer dribbling exercises that can be applied to players. This research is a research development or Research and Development. The method used is the ADDIE model, but it was modified to ADD, considering the current conditions that are currently in the Covid-19 pandemic which allows for social restrictions in direct interaction with players, this is done due to time and cost constraints. ADDIE research into ADD The development of variations of this exercise is carried out in several stages, namely: 1) needs analysis (Analysis), 2) exercise variation design (Design), 3) product development by validating experts and revisions (Develop). In this study, there was no product trial because the situation was not possible, so the author modified the method used by needs analysis to obtain information by using interviews. Meanwhile, the instrument for validation is using a questionnaire and assessment. The results of this study indicate that variations in soccer dribbling training are appropriate to be used as a guide for variations in soccer dribbling training for coaches